La Cour suprême et le rapatriement de la constitution : l'impact des perceptions différentes de la question - Blache, Pierre (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1981)
The following comment is an attempt to encompass the main features of each trend underlying the Court's opinions on matters submitted and decided. According to the author, the members of the bench were at odds on 1° how broad the consensus had to be amongst the provinces whose consent to the federal scheme was at issue; 2° the proper finality envisaged by the federal plan ; 3° the choice of the competent deciding authority.